TEACHING LISTENING SKILL ON A METACOGNITIVE BASIS: PROBLEMS AND SOLUTIONS - Husnatul Hamidiyyah Siregar; Apri Wardana Ritonga; Rendi Pramadi (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
تعليم مهارة الإستماع على أساس ما وراء المعرفية: المشكلات والحلولصعوبة فهم الطلاب للفظ الأصوات المسموعة والمعنى أو المعلومات المسموعة واستكمال الجمل أو المحتوى المسموع يسبب المشاكل في عملية تعليم مهارة الاستماع في الجامعة. الأهداف من هذا البحث هي وصف عملية التعلم الخاصة بمهارة الاستماع في قسم تعليم اللغة العربية بجامعة الإسلامية الحكومية بادانج سيدمبوان ويصف الأنماط واستراتيجياتها من خلال أساس وراء المعرفة. استخدام هذا البحث تصميم البحث النوعي، باستخدام الملاحظات والمقابلات والدراسات الميدانية. نتائج هذا البحث هي؛ أ) عدم توافق الأهداف الموضوعة مع مستوى قدرة الطلاب، ب) توجد ثغرات في إستراتيجية وطريقة مستخدمة مع تطور وسائل الإعلام التكنولوجية اليوم، والتنوع غير الكافي للوسائط التي تدعم عملية التعلم، ج) نموذج التقويم المستخدم هي تقليديً الذي قليل من التطوير باستخدام تطبيقات الفيديو. تعليم مهارة الاستماع باستخدام أساس وراء المعرفية التحكم في عملية التفكير وتنظيمها والتحكم فيها. استخدام منهج وراء المعرفية على الطلاب في الجامعي خيار في حل مشكلة مهارة الاستماع. TEACHING LISTENING SKILL ON A METACOGNITIVE BASIS: PROBLEMS AND SOLUTIONScontent causes problems in the process of teaching listening skills at the university. The objectives of this research are to describe the learning process of listening skills in the Department of Arabic Language Education at the State Islamic University of Padangsidimpuan and to describe the patterns and their strategies through a metacognitive foundation. This research used a qualitative research design, using observations, interviews, and field studies. The results of this research are the problems of listening skills in the Department of Arabic Language Education at State Islamic University Padangsidimpuan; (a) the incompatibility of the goals set with the level of student ability; (b) there is a gap in the maharah istima' strategy and method that is used with the development of today's technological media, and the inadequate variety of media to support the learning process; and (c) the evaluation model used is still conventional although there has been a slight development using video applications. Teaching the listening skill using a metacognitive basis to control, organize and control the thinking process. The use of a metacognitive approach on university students as a choice in solving the problem of listening skills.